An experimental study of Air-demand ratio in free-surface gated circular conduits - Demirel, I. H.; Ozkan, F. (Iwa Publishing, 2022)
Aeration is the process by which the area of contact between water and air is increased, either by natural methods or by mechanical devices. This study investigated the most suitable design to provide a maximum air-demand ratio in the case of free surface flow in gated circular conduits. In the experiments performed for this purpose as the parameters affecting the air demand ratio, the air inlet of each air vent was measured by opening air vents at regular intervals downstream for different conduit openings and different lengths of conduits for air-demand ratio depending on flow rates. In the study, it was observed that the air-demand ratios increased with the increase of the Froude number in all air vents. Although the Q(a)/Q(w) value was found to be 0.28 in.the 6 m conduits for the best air demand rate of 2.5% gate opening, the location of the air vent did not have a significant effect on the air-demand ratio. As a result, it has been understood that the suction downstream of the gated conduit flows does not show a local change. It is thought that the air sucked from the air vents is formed by the drag effect of the water.
Keywords: air-demand ratio; air vent; conduit; free-surface flow